OBSERVATIONAL STUDY ON POISON CASES IN A TERTIARY CARE HOSPITAL - A., RAMYA; G., ANDHUVAN; V., RAGHUPATHI (International Journal of Pharmacy and Pharmaceutical Sciences, 2019)
Objective: To evaluate the prevalence, pattern, and cause of poisoning. To characterize the poisoning cases admitted in a tertiary care hospital; followed by the outcome and to observe the antidote given for the poison cases. Methods: This observational study was undertaken in emergency departments (EMD) and Medical Record Department (MRD). Totally 557 poison cases was recruited in this study. Grade of poison was assessed by using poison severity score. Statistical analysis was done by using Statistical Package for Social Sciences (SPSS). Results: A total of 557 poison cases were identified in 2, 39, 828 patients out of which 360(64%) were suicidal and 189(34) cases admitted were accidental. The patients who were admitted between 2-5 h after exposed to poison were found to be more followed by 0-1 hr,>1-2 h,>6-24 h,>24 h and>5-6 h. More number of cases were seen in the others (Synthetic cow dung powder and medicine) type of poison 296(53%) followed by household poisoning 93(17%), bites 86 (15%), insecticide poisoning 64(12%) and food poisoning 16(3%). Activated charcoal was the maximum used antidote. Conclusion: Through this study, it was found that suicidal poisoning was the most common type.